Artificial drainage devices for glaucoma surgery: an overview - Chaudhry, M; Grover, S; Baisakhiya, S; Bajaj, A; Bhatia, M S (Nepalese Journal of Ophthalmology, 2012)
Artificial drainage devices (ADD) create an alternative pathway for aqueous drainage from the anterior chamber of an eye through a tube to the subconjunctival bleb connected to an equatorial plate under the conjunctiva. The ADDs, both valved and non-valved, are available for end stage or refractory glaucoma. Currently, some of these devices, particularly the Express shunt, are recommended for the primary treatment of glaucoma. In this article, we highlight various ADDs, their indications and contraindications, surgical techniques and associated complications. DOI: http://dx.doi.org/10.3126/nepjoph.v4i2.6547 Nepal J Ophthalmol 2012; 4 (2): 295-302